2013
DOI: 10.1016/j.devcel.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

CASZ1 Promotes Vascular Assembly and Morphogenesis through the Direct Regulation of an EGFL7/RhoA-Mediated Pathway

Abstract: Summary The formation of the vascular system is essential for embryonic development and homeostasis. However, transcriptional control of this process is not fully understood. Here we report an evolutionarily conserved role for the transcription factor CASZ1 in blood vessel assembly and morphogenesis. In the absence of CASZ1, Xenopus embryos fail to develop a branched and lumenized vascular system, and CASZ1-depleted human endothelial cells display dramatic alterations in adhesion, morphology, and sprouting. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 53 publications
5
72
0
Order By: Relevance
“…1I-L). Given that it is not technically possible to investigate nuclear domains in cardiac tissue in vivo, we examined the compartmentalization of CASZ1 in human primary endothelial cells (HUVECS), a cell type previously shown to express CASZ1 (Charpentier et al, 2013b).…”
Section: Casz1 Is Expressed In the Developing Myocardiummentioning
confidence: 99%
See 1 more Smart Citation
“…1I-L). Given that it is not technically possible to investigate nuclear domains in cardiac tissue in vivo, we examined the compartmentalization of CASZ1 in human primary endothelial cells (HUVECS), a cell type previously shown to express CASZ1 (Charpentier et al, 2013b).…”
Section: Casz1 Is Expressed In the Developing Myocardiummentioning
confidence: 99%
“…Cell culture HUVECS (Lonza) were maintained and immunostained as previously described (Charpentier et al, 2013b).…”
Section: Histological Sectioning and Immunohistochemistrymentioning
confidence: 99%
“…[14][15][16] We have recently further implicated RhoA-mediated signaling in vascular development by showing that RhoA lies downstream of a transcriptional cascade involving the transcription factor CASTOR (CASZ1) and its direct target Epidermal Growth Factor-like Domain 7 (Egfl7). 17,18 CASZ1 is an evolutionarily conserved transcription factor originally characterized in Drosophila to maintain neural stem cell identity. 19,20 In addition to expression domains in the brain, Casz1 transcripts have been identified in cardiovascular tissues across vertebrate species, and work from our lab demonstrated that CASZ1 is required for Xenopus cardiogenesis by regulating cardiomyocyte differentiation.…”
mentioning
confidence: 99%
“…19,20 In addition to expression domains in the brain, Casz1 transcripts have been identified in cardiovascular tissues across vertebrate species, and work from our lab demonstrated that CASZ1 is required for Xenopus cardiogenesis by regulating cardiomyocyte differentiation. 17,[21][22][23] Furthermore, genome-wide association studies have revealed a genetic link between the human Casz1 locus and high blood pressure implicating CASZ1 in cardiovascular disease as well as development. 24 Through the use of Xenopus and human endothelial cell models, we have recently demonstrated that CASZ1 is also required for blood vessel development.…”
mentioning
confidence: 99%
See 1 more Smart Citation